Ensaio pré-clínico do composto anticonvulsivante bromo-benzaldeído semicarbazona em ratos e cães - Gioconda Alves de Assumpcao (2007)
Despite the availability of wide range of anticonvulsant drugs, at least 25% of patients continue to have seizures. Furthermore, among those in whom seizures are effectively inhibited, substantial number of patients experience persistent and undesirable effects of these drugs. BrBS is a semicarbazone compound that has shown to possess excellent anticonvulsant activity in rats, besides their low or absent neurotoxicity. The objective of this present study was examine the ability of BrBS to prevent audiogenic seizures (AS) in Wistar Audiogenic Rats (WAR) and seizures induced by Pentilenetetrazole (PTZ) in Wistar rats and mongrel dogs. The behaviors observed in the WARs were severity index (IS), latency to the first wild running episode (FR), latency to the tonic-clonic phase (TCS) and the presence or absence of these seizurecomponents. The endpoints used to evaluate the threshold for PTZ in ratswas the first myoclonic twitch (MT), partial clonus (PC) and generalized tonicclonic seizure (TCS). In dogs, PTZ model was evaluated by the threshold for generalized myoclonic twitch (MT) and partial clonus (PC). In the AS, the maximum dose of BrBS tested (400 mg/kg) blocked all the seizure components (IS = 0) for all animals and no adverse effect was noted. At the dose of 200 mg/kg, BrBS suppress the FR in 43% of rats and only 28 % still showed the TCS. The doses of 100 and 150 mg/kg, BrBS suppressed 50 % of the TCS in the rats. In the PTZ model in rats a restricted dose response was found for the three behaviors tested. No proconvulsant properties were observed. At the doses of 150 and 200 mg/kg, BrBS effectively increased the threshold for MT. The effective dose for PC and TCS was 200 mg/kg. The 11 anticonvulsant effect decreased at 400 mg/kg for MT and TCS components.The mongrel dogs showed to be a suitable model for PTZ seizures studies. However, BrBS showed no anticonvulsant efficacy in this model. Two groups of animals were characterized in their responses to BrBS anticonvulsant activity. These results suggest the existence of animals with individual differences in pharmacological anticonvulsant responses. In conclusion, this study showed the pharmacology efficacy of BrBS against AS in WAR model, against partial and generalized seizure in PTZ model in rats and no activity against PTZ model in dogs.